CONCEPTS PHÉNOMÉNOLOGIQUES ET TYPOLOGIE DE L’EXPÉRIENCE - MOCAN, Raluca (Studia Universitatis Babeș-Bolyai Philosophia, 2016)
Phenomenological Concepts and Typology of Experience. This paper aims at discussing Husserl’s perspective on conceptual identification of the essence of both material and ideal objects. Our starting assumption is that perceptive synthesis provides a foundation for logical synthesis that allows identifying an object, according to phenomenological approach. By analysing a few chosen texts from Ding und Raum, Ideen I and Erfahrung und Urteil, we shall study the distinctions between morphological and exact essences. This will allow for the grasping of the specific character regarding typological concepts. This very clarification is the source of possibility for the phenomenology itself as a descriptive theory on the essence of pure acts (Erlebnisse).